Legal Protection Against Consumers at Drugs That Do Not Have a Distribution Permit - Ermita Faradilla; A. Asmah; Hiksyani Nurkhadijah (Manunggal Halim Jaya, 2022)
This study aims to determine how the legal protection for drug consumers without a distribution permit at the Makassar Drug and Food Control Center and to find out what factors cause drugs without distribution permits. This study uses empirical legal research methods, namely legal research that seeks to see the law in a real sense or can be said to see, examine how the law works in society. Empirical research methods can be said that legal research is taken from the facts that exist in a society, legal entity, or government agency. The results of this study indicate a form of legal protection for drug consumers without a distribution permit at the Makassar Drug and Food Control Center by carrying out pre-market and post-market supervision, both supervisions carried out from the inspection substance group, namely inspection and action group by conducting intelligence operations and providing criminal sanctions. and administration for perpetrators. The factors that cause drugs that do not have a distribution permit are abuse factors, lack of education about the dangers of drug abuse, business actors who do not have the expertise and authority. Recommendations for research by BPOM as an authorized institution should further improve its supervision in this case. The cooperation between the local government and the community is also expected to take part and be actively involved in the implementation of the supervision of drugs and foods that do not have distribution permits.